The Effect of Leaflet-Based Education on Adolescents’ Perceptions of HIV/AIDS at Samarinda Health Vocational School - Maulidya, Vina; Tari, Christy Putri; Pratini, Resni; Sari, Dwi Indah Puspita (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The increasing prevalence of HIV/AIDS among adolescents remains a significant public health concern and is closely linked to inadequate knowledge and persistent misconceptions regarding transmission risks and prevention strategies. Adolescents represent a vulnerable population due to limited access to accurate sexual health information and the influence of social stigma surrounding HIV/AIDS. Data obtained from the Samarinda City Health Center revealed a total of 48 confirmed HIV cases recorded between January and December 2025 among individuals aged 16–54 years, indicating the continued transmission risk within the community, including school-aged populations. This community service initiative aimed to improve the knowledge, attitudes, and perceptions of students at the Samarinda Health Vocational School through the implementation of innovative health education using leaflet-based media. Leaflets were designed to present clear, concise, and easily understandable information related to HIV/AIDS transmission, prevention, and risk behaviors, making them suitable for adolescent audiences. A correlational study with a cross-sectional design was employed to evaluate the effectiveness of this educational intervention. Data were collected using structured questionnaires administered to 22 student respondents before and after exposure to the leaflet media. Statistical analysis was conducted using the Wilcoxon Signed Rank Test to assess changes in perception scores. The results demonstrated a statistically significant improvement in the mean perception score, which increased from 7.91 prior to the intervention to 10.36 following the educational session (p = 0.000). These findings indicate that leaflet-based education is highly effective in enhancing adolescents’ perceptions and understanding of HIV/AIDS prevention.